EVALUASI DAN PERBAIKAN KUALITAS PROSES PRODUKSI DENGAN PENDEKATAN LEAN SIX SIGMA - Rahayu, Sri; Eliyah Yuliana, Pram (Widya Warta, 2018)
CV. Asia Plastics is a manufacturing company engaged in the field of plastic packaging. In the initial picture there are still activities that are not worth adding and the percentage of defects is high enough. Therefore, the purpose of this study was to evaluate and improve the existing production process in order to reduce defect and non value added activity (NVA) which was waste. This method could be done by using Lean Six Sigma Approach and DMAIC (Define, Measure, Analyze, Improve and Control) Steps. Once identified, the all types of waste appearing in the production process were 5 liter jerry consisting of inventory waste, waste motion, waiting waste, overproduction waste, and defect waste. The initial sigma value of the firm for blow 5 was 3.89, the total initial lead time obtained from the value stream mapping (current state) was 405.14 s and the total NVA obtained from the value stream mapping (current state) was 11.706 s. The calculation result after making improvement for Blow 5 showed that the sigma value increased to 4.1, total lead time obtained from value stream mapping (future state) decreased to 293,78 s and total NVA obtained from value stream mapping (future state) decreased to 9,607 s.